Mineral complex additive for concrete - Akhmednabiev, Rasul; Demchenko, Oksana; Ilchenko, Volodymyr; Hukasian, Olha; Gasanov, Elgiz; Lykhach, Dariia (Academic journal Industrial Machine Building Civil Engineering, 2024)
Methods of accelerating the hardening of Portland cement without heat-moisture treatment, in the presence of complex chemical additives - hardening accelerators and finely dispersed crystallization centers, were considered. The study was divided into several stages, where the effect of each accelerator additive on the cement hardening process was investigated. Based on the results, both single and complex chemical additives were selected to accelerate the hardening of cement. The effect of finely dispersed crystallization centers on the cement hardening process was also investigated. Metakaolinite (palygorskite) was used as a dispersed additive, which was synthesized by the authors using kaolin clay and insoluble magnesium compounds and sulfate aqua complexes, iron-sodium alum. The effect of complex additives in various combinations on the properties of cement dough and hardened cement is presented. The optimal composition of additives is proposed, the use of which in combination with technological methods for manufacturing concrete products can provide an energy-saving effect in the production of building structures.
Keywords: additives-cement hardening accelerators; crystallization seeds; cement structuring; sulfate alums